Taxonomic, Spatial and Temporal Patterns of Bleaching in Anemones Inhabited by Anemonefishes - Hobbs, Jean-Paul A. (Public Library of Science, 2013)
BACKGROUND: Rising sea temperatures are causing significant destruction to coral reef ecosystems due to coral mortality from thermally-induced bleaching (loss of symbiotic algae and/or their photosynthetic pigments). Although bleaching has been intensively studied in corals, little is known about the causes and consequences of bleaching in other tropical symbiotic organisms. METHODOLOGY/PRINCIPAL FINDINGS: This study used underwater visual surveys to investigate bleaching in the 10 species of anemones that host anemonefishes. Bleaching was confirmed in seven anemone species (with anecdotal reports of bleaching in the other three species) at 10 of 19 survey locations spanning the Indo-Pacific and Red Sea, indicating that anemone bleaching is taxonomically and geographically widespread. In total, bleaching was observed in 490 of the 13,896 surveyed anemones (3.5%); however, this percentage was much higher (19–100%) during five major bleaching events that were associated with periods of elevated water temperatures and coral bleaching. There was considerable spatial variation in anemone bleaching during most of these events, suggesting that certain sites and deeper waters might act as refuges. Susceptibility to bleaching varied between species, and in some species, bleaching caused reductions in size and abundance. CONCLUSIONS/SIGNIFICANCE: Anemones are long-lived with low natural mortality, which makes them particularly vulnerable to predicted increases in severity and frequency of bleaching events. Population viability will be severely compromised if anemones and their symbionts cannot acclimate or adapt to rising sea temperatures. Anemone bleaching also has negative effects to other species, particularly those that have an obligate relationship with anemones. These effects include reductions in abundance and reproductive output of anemonefishes. Therefore, the future of these iconic and commercially valuable coral reef fishes is inextricably linked to the ability of host anemones to cope with rising sea temperatures associated with climate change.